Laboratory Astrophysics (Astrophysics and Space Science Library,, 2018)
This book focuses on the most recent, relevant, comprehensive and significant aspects in the well-established multidisciplinary field Laboratory Astrophysics. It focuses on astrophysical environments, which include asteroids, comets, the interstellar medium, and circumstellar and circumplanetary regions. Its scope lies between physics and chemistry, since it explores physical properties of the gas, ice, and dust present in those systems, as well as chemical reactions occurring in the gas phase, the bare dust surface, or in the ice bulk and its surface. The book provides adequate material to help interpret the observations, or the computer models of astrophysical environments. It introduces and describes the use of spectroscopic tools for laboratory astrophysics. Each chapter provides the necessary mathematical background to understand the subject, followed by a case study of the corresponding system. This book is mainly addressed to PhD graduates working in this field or observers and modelers searching for information on ice and dust processes.